The effect of organic acid and sodium chloride dips on the shelf-life of refrigerated Irish brown crab (Cancer pagurus) meat. (December 2018) - McDermott, A.; Whyte, P.; Brunton, N.; Lyng, J.; Fagan, J.; Bolton, D.J.
Abstract: Crab ( Cancer pagurus ) meat (white and brown) has a short shelf-life. Chemical treatments may inhibit microbial spoilage and extend shelf-life. The effect of 5% organic acids (lactic acid (LA), acetic acid (AA) and citric acid (CA)) and 5% sodium chloride (NaCl) on TVC (mesophiles and psychrophiles), Enterobacteriaceae, Pseudomonas spp. and lactic acid bacteria (LAB) were investigated during storage (2 °C for 12 days). AA was the most effective treatment for white meat, reducing the initial TVCm and TVCp by 1.6 and 1.8 log10 cfu/g, respectively, and extended the shelf life to 8–11.5 days, compared to 5 days for untreated control samples. LA treatment also significantly (P < 0.05) reduced the initial TVC, but the shelf life was only increased by 3 days. CA and NaCl treatments had no significant effect (P > 0.05). A similar pattern was observed for brown meat samples, although the shelf life was increased by a maximum of 1–3 days. The growth of Enterobacteriaceae, Pseudomonas spp. and LAB was significantly (P < 0.05) reduced on AA treated samples only. It was concluded that the shelf-life of crab meat may be extended by up to 3 days using lactic acid and more than doubled using acetic acid. Highlights: Lactic acid (5%, v/v) increased the shelf-life by 3 days. Acetic acid (5%, v/v) more than doubled the shelf-life. Citric acid (5%, v/v) and sodium chloride (5%, w/v) treatments did not affect shelf-life.